The Effect of Capital Adequacy Ratio and Sukuk Sales on Profitability at Bank Muamalat - Puspa, Chairunnisa Dian; Harahap, Muhammad Ikhsan; Yanti, Nursantri (Journal La Sociale, 2024)
This research purpose is to provide empirical evidence regarding the influence of the Capital Adequacy Ratio (CAR) and Sukuk sales on profitability at Bank Muamalat in 2018-2022. The independent variables in this research are the Capital Adequacy Ratio (CAR), sukuk sales and the dependent variable is profitability. This research uses secondary data obtained from Bank Muamalat’s financial reports. The population in this research is the annual financial report of Bank Muamalat for 2018-2022. The samples used in this research were 60 samples. The analytical method used is multiple linear regression analysis with the help of Eviews 13 and SPSS 25 software. The research results show (1) partially the the Capital Adequacy Ratio (CAR) has a positive and significant effect on profitability with a significant value of 0,032. (2) partially, Sukuk sales have a positive and significant effect of 0,004. (3) simultaneously the Capital Adequacy Ratio (CAR) and sukuk sales influence profitability with a calculated F value of 44,816 so that F calculated > F table, namely 44,816 > 3,16 and it can be seen from the Determination Test (R2) which states that the variables Capital Adequacy Ratio (CAR) and Sukuk sales simultaneously (ROA), namely 13,6%, while the remaining 86,4% is explained by other variables not included in this research model.